Interaction patterns in exploratory learning environments for mathematics: a sequential analysis of feedback and external representations in Chinese schools. Issue 7 (3rd October 2021) - Zhang, Jingjing; Gao, Ming; Holmes, Wayne; Mavrikis, Manolis; Ma, Ning
ABSTRACT: Feedback in exploratory learning systems has been depicted as an important contributor to encourage exploration. However, few studies have explored learners' interaction patterns associated with feedback and the use of external representations in exploratory learning environments. This study used Fractions Lab, an exploratory learning environment for mathematics, to facilitate children's conceptual understanding of fractions in three Chinese schools. Students ( n = 189) from six different classes were invited to use Fractions Lab, and 260, 000 event logs were collected. Beyond demonstrating the overall efficacy of the approach, lag sequential analysis supported us in approaching a deeper understanding of patterns of interaction. The findings highlight that the design of three-levels of feedback (Socratic, guidance, and didactic-procedural feedback) played different roles in supporting students to use external representations to perform mathematical tasks in an exploratory learning environment. This study sheds light on how these interaction patterns might be applied to the Fractions Lab system in order to provide increasingly tailored support, based on cultural differences, to enhance students' technology-mediated learning experiences.